Peningkatan Kapasitas Santriwati dalam Upaya Pencegahan dan Pengendalian Anemia - sudirman, sitti patimah; Sitti Nurana; Elis; Nurul Faimah; Munir, Nur wahyuni (Universitas Aufa Royhan Di Kota Padangsidipuan, 2026)
DDI Al-Ihsan Islamic Boarding School offers both academic and non-academic programs (Tahfidz and Kitab). However, female students in the non-academic program have not received any services related to anemia prevention and control, while those in the academic program have received iron–folic acid (IFA) supplementation, but had not received any education on anemia, therefore 18.5% were still found to be anemic. This community engagement activity aimed to enhance students’ knowledge, awareness, and motivation in preventing and managing anemia through interactive education sessions using multimedia tools (PowerPoint and LCD). The activity involved 30 female students from both academic and non-academic programs, delivered through two sessions lasting approximately 100 minutes in total. The results indicated significant improvements in students’ knowledge (13±0.5 to 15.6±2.6; p = 0.002) and awareness (9.2±2.2 to 11.2±1.1; p = 0.000), while motivation showed a slight, non-significant increase (26.2±4.3 to 27.6±4.7; p = 0.182). In conclusion, the educational intervention contributed positively to strengthening students’ capacity in anemia prevention and control. Further evaluation is recommended to assess its effects on dietary practices, supplementation adherence, and anemia prevalence among female students.